NAGORNO-KARABAKH CONFLICT: EGAL ASPECTS OF A SETTLEMENT - ALIEV, Namig (CENTRAL ASIA AND THE CAUCASUS, 2005)
Any international conflict can be resolved only when the world community makes an objective political and legal assessment of that conflict. A thorough study of the root causes of the confrontation and a comprehensive analysis of the current situation is absolutely essential for: (1) The adoption of a fair decision by the parties (with the participation of mediators).(2) Legally correct and effective use of generally recognized rules of international law; and(3) the establishment of a stable and lasting peace guaranteed by the international community as represented by authoritative international organizations such as the United Nations, OSCE, European Union, Council of Europe, NATO and others. Their immediate duty is to maintain and restore peace and stability both on a global scale and in various parts of the world, and to apply sanctions against the aggressor state. On 25 January 2005, the Parliamentary Assembly of the Council of Europe adopted its Resolution 1416 (2005), “The Conflict over the Nagorno-Karabakh Region Dealt with by the OSCE Minsk Conference”1 (rapporteur David Atkinson). In this document, the Assembly ac-knowledges the occupation of a significant part of Azerbaijan’s territory by Armenian troops and reiterates that “the occupation of foreign territory by a member state constitutes a grave violation of that state’s obligations as a member of the Council of Europe.” Consequently, this resolution can be hopefully regarded as the first, albeit belated, step in this direction. Such documents containing a political and legal assessment of the Nagorno-Karabakh conflict should also be adopted by other international organizations, primarily the OSCE, which provides the framework for the ongoing Minsk negotiation process. The lack of an objective assessment does not encourage the parties to the conflict to show goodwill for the purpose of resolving it and serves (as is the case today) to prolong the confrontation and to create illusions among certain forces that in this way it is possible to overstep the rules of international law, to occupy a sovereign state’s internationally recognized territory and, once these acts have been committed, to draw the de-sired dividends from the negotiation process. It should be remembered that Azerbaijan and Armenia signed the Helsinki Final Act, so recognizing, in accordance with their constitutions, the supremacy of the provisions of this Act in both internal and external legal relationships and the principles of inviolability of borders and territorial integrity of states. Only an objective position of the world community will make it possible to withdraw the armed forces deployed in the conflict zone and to resolve the conflict by peaceful means, without military pressure, on the basis of the principles of international law.